S, PENERAPAN PASAL MAKAR 106 KUHP JO 55 AYAT (1) KUHP PERKARA ALEXANDER WORLAKA - MUHAMMAD SENANATHA PURUSADHIKARA HAMZAH PUTRA (AL WASATH Jurnal Ilmu Hukum, 2023)
The Republic of South Maluku is an organization that is prohibited by the Civil Emergency Decree concerning the Activities of the Maluku Sovereignty Front Organization of the Republic of South Maluku, which discusses the existence of the Republic of South Maluku when the State of Indonesia was originally formed, and to this day according to law and statutory provisions, the Republic of South Maluku is an organization that is prohibited because its purpose is treason in the sense of wanting to separate itself from the Unitary State of the Republic of Indonesia. Decision Number 69/Pid.B/2021/PN Drh proves that there are still individuals who are trying to gather power to proclaim the Republic of South Maluku as a state. The author will discuss the analysis of evidence and the application of Article 106 of the Criminal Code Jo 55 paragraph (1) of the Criminal Code in the case of the crime of treason against.